Implementation of Sea Transportation Policy (Analysis of the Klotok Boat Sea Transportation Policy in the Penajam - Balikpapan Route) - Dini Rahma Sari; Muliyadi Hamid; Yunus, Mujahid (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2025)
This research aims to analyze the implementation of the klotok boat sea transportation policy on the Penajam-Balikpapan route in supporting community mobility and economic activities. Furthermore, this study also seeks to analyze the factors supporting the implementation of said policy. These objectives are aligned with the endeavor to gain a comprehensive understanding of the policy in question. This study adopts a qualitative approach, with data collection conducted through in-depth interviews with various relevant parties, including policymakers, operators, and community users. The collected data were then thematically analyzed to identify key patterns and themes, thereby providing an in-depth understanding of the phenomena under investigation. The research findings indicate that the implementation of the klotok boat policy is highly effective in providing an affordable and efficient alternative transportation solution, while significantly empowering the local economy. This mode of transportation successfully meets the urgent needs between Penajam and Balikpapan, offering a travel time of approximately 45 minutes and a fare of Rp 10,000/passenger, contributing to transportation cost savings and demonstrating stable daily occupancy rates. Its success is also supported by an increase in boat owners' income (30-40%) and the creation of over 120 new jobs. In conclusion, the main supporting factors for the implementation of the Sea Transportation Policy for Klotok Boats in Penajam - Balikpapan are the urgent community need for alternative transportation, the positive disposition of implementers and users, and an organized bureaucratic structure. This urgent need, support for the local economy, and the strategic potential in the development of IKN are key drivers. Despite resource limitations such as an aging fleet and limited dock capacity, the commitment of operators and public acceptance are essential for the sustainability and effectiveness of the klotok boat sea transportation policy's implementation.